2016
DOI: 10.1007/s13370-016-0449-5
|View full text |Cite
|
Sign up to set email alerts
|

Pell numbers with the Lehmer property

Abstract: Abstract. In this paper, we prove that there is no number with the Lehmer property in the sequence of Pell numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Thus, McDaniel's result applies for us showing that 4 | q − 1 | φ(P n ) | P m , so 4 | m by Lemma 2.2. Further, it follows from a the result of the second author [5], that φ(P n ) P φ(n) . Hence, m φ(n).…”
Section: Some Lower Bounds On M and ω(P N )mentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, McDaniel's result applies for us showing that 4 | q − 1 | φ(P n ) | P m , so 4 | m by Lemma 2.2. Further, it follows from a the result of the second author [5], that φ(P n ) P φ(n) . Hence, m φ(n).…”
Section: Some Lower Bounds On M and ω(P N )mentioning
confidence: 94%
“…For example, in [11], it is shown that 1, 2, and 3 are the only Fibonacci numbers whose Euler function is also a Fibonacci number, while in [4] it is shown that the Diophantine equation φ(5 n − 1) = 5 m − 1 has no positive integer solutions (m, n). Furthermore, the divisibility relation φ(n) | n − 1 when n is a Fibonacci number, or a Lucas number, or a Cullen number (that is, a number of the form n2 n + 1 for some positive integer n), or a rep-digit (g m − 1)/(g − 1) in some integer base g ∈ [2,1000] have been investigated in [10,5,7,3], respectively. Here we look for a similar equation with members of the Pell sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers concentrated on proving that there are no numbers with the Lehmer property in certain in sequences of positive integers like the sequences of Fibonacci and Lucas numbers [3,1]. In [5,6], it was shown that there are no numbers with the Lehmer property in the sequence of Cullen numbers and in generalized Cullen numbers.…”
Section: Introductionmentioning
confidence: 99%
“…In [5,6], it was shown that there are no numbers with the Lehmer property in the sequence of Cullen numbers and in generalized Cullen numbers. Also, in [7] it was proved that there is no number with the Lehmer property in the sequence of Pell numbers. Also, in [9] it was proved that there is no Lehmer number of the form g n −1 g−1 for any n > 1 and 2 ≤ g ≤ 1000.…”
Section: Introductionmentioning
confidence: 99%
“…The upper bound given by Pomerance was a crucial step in proofs of many results concerning the existence of Lehmer numbers in certain sequences, such as the Fibonacci sequence [6], Pell numbers [3] or Cullen numbers [4,5].…”
Section: Introductionmentioning
confidence: 99%